Rancang Bangun E-RT dalam Upaya meningkatkan Keamanan, Ketertiban, dan Kerukunan Hidup Antar Warga - Bachtiar, Yogi; Anjani, Dewi; Novianti, Desi (Jurnal Teknologi Terpadu, 2022)
E-RT is a development of E-Government to improve public services so that people in the surrounding environment can more easily access information. One of the functions of the RT is to create security, order and harmony in its environment. One of the rules can realize this safety and order: guests must report 1x24 hours. However, the lack of public awareness of this rule causes this regulation not to be implemented. So this study aims to develop e-RT applications in the field of security and order to increase effectiveness and efficiency, especially in reporting guests who come to the RT environment. The approach used is qualitative with a descriptive method. The study results are in the form of an e-RT application that residents and RT administrators can access. In this study, the application's design is based on user needs analysis, where data collection uses the interview method. In visualizing and building application model concepts, this research uses UML. And it is testing the application using the black box method. The test consists of 7 scenarios; In the initial examination, there were errors in scenarios three and seven, so the test's success was only 80%. After scenarios 3 and 7 are fixed, especially in the coding section, the application can run 100% according to its needs or functions.